Level of Difficulty in Implementing The Field Experience Program Teaching Physical Education - Yulianti, Mimi; Makorohim, M. Fransazeli; Nasution, Rizqi Murdiana (Universitas Negeri Semarang, 2020)
The purpose of this study is to determine the level of difficulty of students in the implementation of the field experience program 2018 school year. This type of research uses quantitative descriptive research. The population in this study was all UIR FKIP health and recreation physical education students students who had finished implementing PPL 2018 school year. The sample in this study amounted to 70 students using the Slovin 10% theory formula. The research instrument used a questionnaire with a number of 58 items, a Likert scale, and analysis data with percentage techniques. The results of this study indicate that the level of difficulty of students in the implementation of PPL academic year 2018. In the components of the learning preparation plan reached 67.67% classified as moderate (few experienced difficulties) and the components of learning activities amounted to 76.18% classified as easy (not so difficult). It can be concluded that after conduction research on students who have completed the field experience program 2018 academic year in the easy category (not so difficult) by having a percentage of 71,92%.